10.61533 DAMPAK BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN : KAJIAN LITERATUR - Martinus Buulolo; Burhanuddin Bani (Jurnal Ilmiah Niaga Bisnis Elektronik, 2025)
Optimal employee performance will be based on a quality organizational culture, providing impact and contributing to the organization to achieve its goals. The purpose of this study is to answer how organizational culture impacts employee performance, what are the various research designs used for employee performance, what instruments are used by researchers to measure employee performance, and what are the data analysis techniques used by researchers to analyze employee performance. Some of the research results contained in this article are using questionnaires in collecting data, with a quantitative research approach, and have target research objects of private employees, government employees, and educational institutions. The results of the study indicate that organizational culture has a positive and significant effect on employee performance and has an impact on the organization to maximize the company's goals and achievements.